Enhancing power quality in a smart grid using dynamic voltage restorer - Jothi, Thangavel; Arun, Manoharan; Varadarajan, Murugesan (International Journal of Applied Power Engineering (IJAPE), 2024)
Hybrid smart grids which depend on renewable energy have substantial challenges to their reliability and efficiency due to power quality issues. However, the performance and dependability of the system might be impacted by power quality concerns caused by the intermittent nature of renewable energy sources and the presence of nonlinear and unbalanced loads. This study suggests that a hybrid renewable energy-based smart grid can improve power quality by using a dynamic voltage restorer (DVR), a flexible alternating current transmission system device. The goal is to improve voltage stability, reduce voltage spikes and harmonic distortion, and provide a clean power supply. This study's primary contributions are the design and execution of the cascaded H-bridge DVR topology, the development of a modified synchronous reference frame-based controller and a thorough examination of the performance of the integrated DVR system. Total harmonic distortion and voltage regulation are two power quality metrics used to evaluate the effectiveness of the suggested technique in MATLAB simulations.